2020
DOI: 10.3390/su12041301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intersecting Angle on Pedestrian Crowd Flow under Normal and Evacuation Conditions

Abstract: Complex pedestrian or passenger crowd movements, such as intersecting movements, can create a bottleneck resulting in delays during emergency escape from public infrastructure such as major public transport hubs. Limited studies have examined the effect of different intersecting angles and walking speeds on pedestrian outflow. This study aims to systematically investigate the effect of different intersecting angles (30 • , 90 • , and 150 • ) and walking speeds (normal walking, faster walking) on pedestrian out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(77 reference statements)
0
2
0
1
Order By: Relevance
“…A striped pattern facilitates overall pedestrian flow by reducing collision-avoidance maneuvers, thereby increasing the average walking speed. Only a few subsequent human studies have tested oblique crossing angles [ 69 71 ], but stripe patterns were not analyzed. The bisector hypothesis thus remains to be tested experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…A striped pattern facilitates overall pedestrian flow by reducing collision-avoidance maneuvers, thereby increasing the average walking speed. Only a few subsequent human studies have tested oblique crossing angles [ 69 71 ], but stripe patterns were not analyzed. The bisector hypothesis thus remains to be tested experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Zhang and Seyfried [ 45 ] indicated that there is no significant difference between the fundamental diagrams of 90° and 180° intersecting angles. Aghabayk et al [ 24 ] considered three crossing angles (30°, 90, and 150°) and two speed levels (normal speed walking and jogging) and concluded that crossing configurations with smaller angles (30° in their experiment) have higher flow rates and smaller evacuation times. Lian et al [ 25 ] conducted an experiment to study four-directional intersecting flows with 364 students.…”
Section: Related Workmentioning
confidence: 99%
“…Aghabayk et al [28] investigated the impact of intersection angles and desired speed on the outflow rate and evacuation time of crossing configurations using the data collected through a controlled experiment. The paper considered three intersection angles, i.e., 30 • , 90 • , and 150 • , and two desired speed levels, i.e., normal-speed walking and jogging.…”
Section: Related Workmentioning
confidence: 99%
“…However, the speed was limited to slow-speed running to ensure the safety of the participants during the experiment. The present study is based on the controlled laboratory experimental data using human subjects collected in 2016 by Aghabayk et al [28], which examines the influence of intersecting angles on pedestrian crowd flow using the aggregate values of the flow rate, speed, evacuation time, and travel time. The present paper provides further in-depth and microscopic analysis of the data to understand the spatial variations in speed within the corridor for intersecting pedestrian streams at varying speed levels.…”
Section: Introductionmentioning
confidence: 99%